The epidemiology and management of postmenopausal osteoporosis: a viewpoint from Brazil - Baccaro, Luiz Francisco (Clin Interv Aging, 2015)
Brazil has an aging population, with an associated increase in the prevalence of chronic diseases. Postmenopausal osteoporosis is of particular concern because it leads to an increased risk of fractures, with subsequent negative impacts on health in older women. In recent years, efforts have been made to better understand the epidemiology of osteoporosis in Brazil, and to manage both direct and indirect costs to the Brazilian health care system. The reported prevalence of osteoporosis among postmenopausal women in Brazil varies from 15% to 33%, depending on the study methodology and the use of bone densitometry data or self-reporting by participants. A diagnosis of osteoporosis can be made on the basis of fractures occurring without significant trauma or on the basis of low bone mineral density measured by dual energy X-ray absorptiometry. To reduce the risk of osteoporosis, all postmenopausal women should be encouraged to maintain a healthy lifestyle, which includes physical activity and a balanced diet. Smoking and alcohol use should also be addressed. Special attention should be given to interventions to reduce the risk of falls, especially among older women. Calcium intake should be encouraged, preferably through diet. The decision to recommend calcium supplementation should be made individually because there is concern about a possible increased risk of cardiovascular disease associated with this treatment. Brazilian women obtain a minimal amount of vitamin D from their diet, and supplementation is warranted in women with little exposure to solar ultraviolet-B radiation. For women diagnosed with osteoporosis, some form of pharmacologic therapy should be initiated. Compliance with treatment should be monitored, and the treatment period should be individualized for each patient. The Brazilian government provides medication for osteoporosis through the public health system free of charge, but without proper epidemiological knowledge, the implementation of public health programs is impaired.